Implementasi Pendidikan Siaga Bencana di SDN Purwosekar - Zenis, Yuli Yana; Abdurrahman, Danang (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Indonesia is a country that has a lot of potential for disasters. The large number of potential disasters should be balanced by human resources who are ready to be prepared in the face of disasters. Therefore, in community service activities, the 2019 State University of Malang Community Service Program held activities in the field of disaster. This activity is the Implementation of Disaster Preparedness Schools which aims to provide education on an early warning system when an earthquake occurs. The activity was carried out Monday and Tuesday, June 24 and 25 2019 at SD Negeri 1 and 2 Purwosekar. The target of these activities is elementary school students in grades 4-6. The arrangement of activities carried out is the provision of material packaged in the form of story telling, singing, games, and simulations. The delivery of the material is packaged as attractive as possible so that it can be accepted by students easily. The results obtained from these activities were the knowledge and experience of students regarding disaster science, especially earthquake preparedness.